Energy Harvesting Wireless Communications - Chuan, Huang 1983- author; Sheng, Zhou author; Jie, Xu author; Zhisheng, Niu author; Rui, Zhang author; Shuguang, Cui author (Hoboken, NJ : John Wiley & Sons, 2019)
Includes bibliographical and references